Borrower- and lender-specific determinants in the pricing of sustainability-linked loans. (20th January 2023) - Pohl, Christian; Schüler, Gregor; Schiereck, Dirk
Abstract: The financial industry has developed a wide breadth of instruments to support the growing number of firms interested in socially responsible, or "sustainable", investing. The use of the most well-known, green bonds, is generally limited to investments defined by the Green Bond Principles. However, more flexible sustainability-linked loans (SLLs) have skyrocketed in importance recently. In 2021, they became the largest corporate debt type including a sustainable feature, raising USD 735 billion globally. Existing evidence on the potential lower yields of green bonds, also known as the greenium, supports their attractiveness from a borrower's perspective. Contrary to this evidence, however, little is yet known about the financial attractiveness of SLLs. We address this research gap, and provide new findings on the yields of sustainability-linked loan financing. We study 121 SLLs originated in 2021, and compare them to peers of matched conventional loans featuring similar characteristics. We find that SLLs are associated with lower initial yields for borrowers. This benefit is more pronounced for borrowers with strong environmental profiles, and for loan originations conducted using a lender syndicate with high environmental standards. The financial benefits, coupled with their flexible structure, suggest that SLLs can be an attractive tool for companies from a variety of sectors to use in managing sustainable business transformations and addressing the challenges of climate change. Highlights: Sustainability-Linked Loans broaden sector participation in sustainable debt market. Sustainability-Linked Loans come with lower initial spreads for borrowers. Spread discount is higher for borrowers with high environmental profiles. Spread discount is higher if lender syndicate has high environmental profile. Spread discount is higher for lender syndicates with low governance profiles.